HeartMate II System Controller Failure Presenting as Driveline Fault With Repeated Pump Stoppages. (July 2019) - Flint, Kelsey M.; Brieke, Andreas; Cornwell, William K.; Pierce, Christopher; Cleveland, Joseph C.; Pal, Jay D.
Abstract : Supplemental Digital Content is available in the text.